Looking at Aesthetic Emotions in Advertising Research Through a Psychophysiological Perspective - Lajante, Mathieu; Droulers, Olivier; Derbaix, Christian; Poncin, Ingrid (Frontiers in Psychology, 2020)
Do usual commercials elicit the full spectrum of emotions? In this paper, we posit that they do not. Concepts and measures related to the adaptive functions and well-being areas of emotion research cannot simply be transferred for use in advertising research. Emotions elicited by affect-laden events as depicted in commercials should not be confused with emotions felt by consumers when exposed to those commercials. This is why “aesthetic” emotions seem more appropriate than “utilitarian” emotions in advertising research, with the former generally felt more significantly than they are acted upon. Aesthetic emotions elicit limited physiological change, and they rely on the intrinsic pleasantness appraisal of commercials. Accordingly, pleasure and displeasure—as observed through expressive and subjective components of aesthetic emotion—often form the first and only step of commercial appraisal, and they are directed toward attitude formation rather than overt behaviors. Our preliminary psychophysiological study shows this by investigating the contributions of psychophysiological and self-reported measures of aesthetic emotions induced by commercials to explain attitudes toward advertisements. The results show that only two components of aesthetic emotion positively influenced attitudes toward the advertisements: expressive (measured by facial electromyography and subjective (measured by the self-assessment manikin scale). Also, the subjective component of aesthetic emotion partially mediates the effects of the expressive components on attitudes toward the ads. Our exploratory study illustrates the relevance of focusing on aesthetic emotions in advertising research. It also shed new light on the contributions of the physiological, expressive, and subjective feelings components of aesthetic emotions in advertising effectiveness.